The hidden foundation : cinema and the question of class - James, David E., 1945-; Berg, Rick. (Minneapolis : University of Minnesota Press, 1996)
Ranging from the earliest days of the cinema to the present, The Hidden Foundation reestablishes class as a fundamental aspect of film history. Featuring prominent film scholars and historians acting to inaugurate a new type of film studies, this volume is unique in its international scope, diversity of perspectives and methodologies, and the cultural, political, and historical sweep of its analysis.
Introduction : is there class in this text? / David E. James -- Beyond the screen : history, class, and the movies / Steven J. Ross -- The melos in Marxist theory / Jane Gaines -- 'Strike' and the question of class / Bill Nichols -- The gun in the briefcase; or, the inscription of class in film noir / Paul Arthur -- "No sin in lookin' prosperous" : gender, race, and the class formations of middlebrow taste in Douglas Sirk's 'Imitation of Life' / Marianne Conroy -- Compromised liberation : the politics of class in Chinese cinema of the early 1950s / Esther C.M. Yau -- Out of the mine and into the canyon : working-class feminism, yesterday and today / Lillian S. Robinson -- For a working-class television : the miners' campaign tape project / David E. James -- Poltergeists, gender, and class in the age of Reagan and Bush / Douglas Kellner -- Class in action / Chuck Kleinhans -- The Hollywood waitress : a hard-boiled egg and the salt of the earth / Jane Callings.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Motion pictures -- Political aspects; Motion pictures -- Social aspects; Social classes; Social Class; Cinéma -- Aspect social; Classes sociales; Cinéma -- Aspect politique; social classes; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- History & Criticism; Motion pictures -- Political aspects; Motion pictures -- Social aspects; Social classes; Filmkunst; Sociale aspecten; Politieke aspecten